AGROCLUSTER SYSTEM AND ITS FINANCIAL CHARACTERISTICS IN THE DEVELOPMENT OF FRUIT GROWING, VEGETABLE GROWING AND VITICULTURE IN UZBEKISTAN. - Takhirjan Ganievich Yokubov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Ensuring uninterrupted food supply to the population of Uzbekistan and economic growth through the export of fruit and vegetable and grape products to the world market is one of the pressing challenges of our time. This article, based on international experience, examines the main features, significance, implementation procedure and financial characteristics of the agro-cluster system being introduced in our country in the development of fruit and vegetable growing, as well as the significance of regulatory documents adopted by our state for the development of the industry.